Men of fire : Grant, Forrest, and the campaign that decided the Civil War - Hurst, Jack (Basic Books, 2008)
Deep in the winter of 1862, on the border between Kentucky and Tennessee, two extraordinary military leaders faced each other in an epic clash that would transform them both and change the course of American history forever. Brigadier General Ulysses S. Grant had no significant military successes to his credit at the outset of the campaign. He was barely clinging to his position within the Union Army--he had been officially charged with chronic drunkenness only days earlier, and his own troops despised him. His opponent was as untested as he was: an obscure lieutenant colonel named Nathan Bedfo.